Defective regulation of L1 endogenous retroelements in primary Sjogren's syndrome and systemic lupus erythematosus: Role of methylating enzymes. (March 2018) - Mavragani, Clio P.; Nezos, Adrianos; Sagalovskiy, Irina; Seshan, Surya; Kirou, Kyriakos A.; Crow, Mary K.
Abstract: Objective: To investigate whether altered DNA methylation contributes to the inappropriate expression of LINE-1 (L1) retroelements in primary Sjogren's syndrome (SS) and systemic lupus erythematosus (SLE). Methods: Minor salivary glands (MSG) were obtained from 42 patients with primary SS [23 without adverse predictors for lymphoma development (SS-low risk), 7 SS-high risk and 12 complicated by B-cell lymphoma (SS-lymphoma)] and 17 sicca controls (SC). Additionally, kidney biopsy specimens and PBMCs were obtained from 23 and 73 lupus patients, respectively. Relative mRNA expression was quantified for full-length L1 transcripts, along with mediators of methylation. In an independent set of 44 MSG samples (11 SS-low risk, 10 SS-high risk, 15 SS-lymphoma and 8 SC), methylation levels of the L1 promoter were determined by bisulphite pyrosequencing. Results: A strong positive correlation was demonstrated between L1 transcripts and gene products that mediate de novo and constitutive DNA methylation, DNA methyltransferase (DNMT)3B, DNMT1, and methyl CpG binding protein 2 (MeCP2), in both SS MSG and lupus renal tissues. A significant negative correlation was observed between expression of L1 and lymphoid-specific helicase (LSH, encoded by HELLS) in both SS MSG and SLE kidney tissues, as well as between DNMT3A transcripts and L1 expression in SLE kidney tissues and PBMCs. Reduced levels of L1 promoter methylation along with increased DNMT3B, DNMT1, and MeCP2, but reduced LSH levels were detected in SS-low risk patients compared to both SS-lymphoma and SC. The SS-lymphoma group was also characterized by a profound decrease of MeCP2 and DNMT3B compared to SC. Conclusion: Our data support a contributory role of altered methylation mechanisms in the pathogenesis of systemic autoimmune disorders and related lymphoproliferative processes and suggest that LSH and DNMT3A should be investigated as candidate upstream mediators of decreased L1 promoter methylation and increased L1 expression. Highlights: Decreased L1 promoter methylation in MSG tissues derived from low risk SS and SLE patients compared to controls. Inverse correlation between expression of the chromatin modelling protein LSH and L1. Coordinate expression of L1 mRNA expression with MeCP2, DNMT1 and DNMT3B in SS and SLE-derived tissues.